Banking sector performance during the COVID-19 crisis - Demirgüç-Kunt, Asli; Pedraza, Alvaro; Ruiz-Ortega, Claudia (Journal of Banking & Finance, 2021)
This paper examines the impact of financial sector policy announcements on bank stocks around the world during the onset of the COVID-19 crisis. Overall, we find that liquidity support, borrower assistance programs and monetary easing moderated the adverse impact from the crisis, but their impact varied considerably across banks and countries. By contrast, countercyclical prudential measures led to negative abnormal returns in bank stocks, suggesting that markets price the downside risks associated with these policies.